Student engagement in English language learning with artificial intelligence (AI) chatbot from the perspective of planned behavior theory - Fauziah; Diana, Novita; Putri , Silvia (Proceder: Applied Linguistics, Literature, and Language Education, 2025)
This qualitative study investigated student engagement in English language learning facilitated by Artificial Intelligence (AI) chatbots, utilizing the Planned Behavior Theory (PBT) lens. Employing a phenomenological approach, this study explored the lived experiences and perceptions of 15 participants enrolled in a private higher education institution in Aceh, Indonesia. Data collection involved semi-structured interviews, focus group discussions, and observation to explore students’ attitudes, social influences, perceived behavioral control, and the alignment of perceptions with engagement. Thematic analysis was applied to analyze the data, revealing students’ attitudes towards AI chatbots influenced by perceptions of utility, social norms, and technological proficiency. The triangulation of findings from interviews and focus groups highlighted converging themes and provided a comprehensive understanding of student engagement with AI chatbots in English language learning. Participants navigated a complex interplay between individual beliefs and external factors in engaging with AI chatbots for language learning. This study emphasizes the importance of considering sociocultural contexts and user experience in designing and implementing AI-driven educational tools. The insights gleaned from this research contribute to the broader discourse on technology-mediated language learning and inform strategies for enhancing student engagement in English language education.